THE EFFECT OF PREHEATING OF COMPOSITE RESIN ON ITS COLOUR STABILITY WHEN IMMERSED IN TEA AND COCA COLA SOLUTION – AN IN VITRO STUDY. - Dr Pankaj Debadwar; Dr Vishal Mahajan; Dr Bhavana Gaikwad; Dr Rohini Mahajan; Dr Sonikumari Jha; Dr Pawan Kothari (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim: Aim of this study was to evaluate the preheating effect of composite resin on its colour stability when immersed in tea and coca cola solutions. Objective: To evaluate the preheating effect of composite resin on its colour stability when immersed in tea and coca cola solutions. Materials And Methods: In this experimental study, 60 disks samples of a nano hybrid composite with a diameter of 5mm and thickness 2mm were prepared using plastic mould. Specimens were divided into two groups. Group 1 of 30 specimens, composite was placed in refrigerator and placed in plastic moulds at room temperature. After condensing, celluloid strips were placed to achieve smooth, glossy surface. Samples were polymerized for 40 seconds. In group 2 of 30 specimens , composite was placed in convection micro oven at temperature of 53 to 680C, the composite was immediately inserted in plastic mould to reduce heat dissipation and cured for 40 seconds. All the samples were unmoulded and placed in 370C distilled water for 24 hours for complete polymerization. Samples were dried with moisture absorbing paper and colour stability was measured (t0). The samples of each group were randomly divided into 3 subgroups ( n=10) and respectively immersed in distilled water, tea and coca cola. Solutions were changed and samples were washed daily. After 30 days, colour stability of all the samples was measured using CIE-L*a*b* system. RESULT. In the preheating group,the highest colour change was observed in tea followed by coca cola and least in water. In the pre cooling group,the highest colour change was observed in tea followed by coca cola and least in water. Preheating is more statistical significantly resistant to colour change as compared to pre cooling for all sub groups i.e. tea, coca cola and water DISCUSSION: Preheating of composite resin rises its degree of polymerization leading to reduced absorption and penetration of the colorant solution causing higher resistance to discolouration. CONCLUSION: The findings of the present study showed that preheating of the composite resin is effective in the reduction of its colour change.